Modelling the Efficacy of Neprilysin from Various Species in Degrading Different Amyloid-β peptides: Potential Application in Development of Therapeutics for Alzheimer’s Disease - Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
Recombinant neprilysin due to its degradation potential against Amyloid-β (Aβ) peptides has been looked at as a potential therapeutic candidate for treating Alzheimer’s disease (AD). However the enzymatic activity of neprilysin against different Aβ peptides can variable which significantly limits the therapeutic optimization. Using the molecular interaction analysis and modelling it against the known enzyme-substrate kinetics, this study developed a novel approach to predicting biosimilar enzyme-substrate kinetics. The known enzyme-substrate kinetics of human recombinant neprilysin with Aβ1-40 peptide was used as the prototype to assess the affinity and efficacy of various inter and intra-species neprilysin- Aβ peptide enzyme kinetics based on the relative molecular interaction analysis. Significant inter and intra-species varia- tions in neprilysin- Aβ peptide enzyme kinetics was observed which further validated the need for optimizing enzyme kinetics tailored to specific substrate degradation. The novel enzyme kinetics modelling approach described in this study can be helpful in the developing of recom- binant enzymes/peptides for personalised therapeutic applications.
Keywords: Neprilysin; Amyloid-β peptides; Receptor pharmacology; Enzyme kinetics; Alzheimer’s disease